2021
DOI: 10.17582/journal.jahp/2021/9.4.425.434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harvesting Time on Tannin Biological Activity in Sambiloto (Andrographis paniculata) Leaves and In vitro Diet Digestibility Supplemented with Sambiloto Leaves

Abstract: This study investigated the effect of harvesting time on concentration and biological activity of tannin in Andrographis paniculata (A. paniculata) leaves and determined the in vitro rumen fermentation and digestibility of diet supplemented with A. paniculata leaves to evaluate its role as herbal supplement in ruminant's feed. A. paniculata leaves were harvested at two time points i.e., before and after flowering phase and the samples were dried to analyze concentration and biological activity of tannin. Rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similarly, diets used in goats [ 80 , 81 ], in treatments including Andrographis paniculata and Piper sarmentosum , respectively, showed a population increase in Fibrobacter succinogenes . In the former, possibly due to the increase in ruminal pH caused by ruminal bacteria, which subsequently provides benefits [ 181 ]. On the other hand, the decrease in Fibrobacter succinogenes populations after the inclusion of Piper sarmentosum suggests that the inhibitory causes of bioactive compounds, such as tannins, affect other gram-positive bacteria, as well as essential oils, which have been shown to inhibit the relative abundance of Fibrobacter succinogenes as with other metagenomic bacteria in the rumen [ 176 ].…”
Section: An Approach To the Functions Of Microorganismsmentioning
confidence: 99%
“…Similarly, diets used in goats [ 80 , 81 ], in treatments including Andrographis paniculata and Piper sarmentosum , respectively, showed a population increase in Fibrobacter succinogenes . In the former, possibly due to the increase in ruminal pH caused by ruminal bacteria, which subsequently provides benefits [ 181 ]. On the other hand, the decrease in Fibrobacter succinogenes populations after the inclusion of Piper sarmentosum suggests that the inhibitory causes of bioactive compounds, such as tannins, affect other gram-positive bacteria, as well as essential oils, which have been shown to inhibit the relative abundance of Fibrobacter succinogenes as with other metagenomic bacteria in the rumen [ 176 ].…”
Section: An Approach To the Functions Of Microorganismsmentioning
confidence: 99%
“…It has been suggested that the bioactive compounds found in Andrographis paniculata play a role in methane reduction. Tannins present in this herb can be used as methane inhibitors [13].…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan may be utilised as a natural rumen modifier because it modifies rumen fermentation in desirable methods, such as increasing propionate and decreasing acetate, which is desirable for higher energy synthesis with possibly minimised methane emission [9]. As herbs, due to the availability of active compounds in Andrographis paniculata, it can be used as a supplement's ingredient [12,13]. As ruminant feed supplements, it is necessary to evaluate the effectiveness of these two component combinations.…”
Section: Introductionmentioning
confidence: 99%